Factors Influencing The Use of Local Government Performance Information: Institutional Theory Perspective - Wia Rizqi Amalia; Akbar, Rusdi (Universitas Teknologi Yogyakarta, 2021)
Performance information is used for strategic planning, budgeting, program management, supervision, and evaluation. This performance information is also reported to the external parties. This study aims to examine the factors that influence the use of local government performance information based on institutional theory perspective. Triangulation methods are used to analyze and interpret data. Hypothesis testing is carried out in the quantitative phase using Partial Least Square, then followed by thematic analysis in the qualitative phase. The results showed that technical and organizational factors did not affect the use of performance information, while cultural factors empirically had a significant effect on the use of performance information. Based on the institutional theory perspective, the use of performance information is driven by institutional isomorphism in the form of coercive, mimetic, and normative pressures. The results of this study are expected to contribute to local governments paying attention to cultural factors in optimizing the use of performance information.